A Third Concept of Liberty : Judgment and Freedom in Kant and Adam Smith. - Fleischacker, Samuel (Princeton University Press, 2001)
Taking the title of his book from Isaiah Berlin's famous essay distinguishing a negative concept of liberty connoting lack of interference by others from a positive concept involving participation in the political realm, Samuel Fleischacker explores a third definition of liberty that lies between the first two. In Fleischacker's view, Kant and Adam Smith think of liberty as a matter of acting on our capacity for judgment, thereby differing both from those who tie it to the satisfaction of our desires and those who translate it as action in accordance with reason or "will." Integrating the thou.